Genocidas ir rezistencija Nr. 17(2) - Matulytė, Margarita; Černeckaitė, Irina; Vitkus, Hektoras; Bubnys, Arūnas; Brandišauskas, Valentinas; Skorupskas, Andrius (Genocidas ir rezistencija, 2005)
Pilnas leidinys (nuskenuota popierinė versija)